Measuring trust component in patient-physician relationship in dermatology/Hekim ile dermatoloji hastalari arasindaki iliflkide guven unsurunun olculmesi - Yilmaz, Sadik; Akkaya, Vahide Baysal (Türkderm, 2009)
Background and Design: Patient's trust is an essential component of the patient-physician relationship. The aim of this study was to measure the level of trust of the patients in physicians, to determine factors affecting trust level and to propose some suggestions in order to improve trust component in patient-physician relationship. Material and Method: Three hundred five patients participated in the survey. A questionnaire was prepared to evaluate the level of patients' trust in physician and satisfaction to the dermatology department and patients' socio-demographic variables. Analyses of data obtained from questionnaires were performed using SPSS (Statistical Package of Social Science), version 15.0. Results: Patients have an average of 3.72 ± 0.54 trust level (out of 5) in their physicians. This reveals the patients have a trust slightly above the medium level for their physicians. There are no statistically significant relationships between the trust level and other socio-demographic variables such as age, sex and income. Patients' satisfaction level towards the dermatology department was 4.17 ± 0.65. There was a positive and statistical significantly correlation between trust and satisfaction. Patients choose more cheerful and well-informed physicians. Trust had been determined as an important factor in the patient-physician relationship. Patients trust well-informed, sympathetic and honest physicians. Nevertheless, disrespectfulness and lack of information had been determined as the most distrusted physician behaviors. Conclusion: Although there are many studies to evaluate this subject in the literature as far as we determine this is the first study in dermatology practice in Turkey. Because there are many chronic diseases in dermatology to provide concordance of patients' treatment and continuity to same physicians or medical clinics may be obtained by building the patient's trust. In this sense, trust component in patient-physician relationship in dermatology must not be neglected. Also must be avoided for the distrusted attitudes and behaviors. (Turkderm 2009; 43: 89-94) Key Words: Dermatology, trust, patient-physician relation Amac: Guven, hasta ile hekim arasindaki iliskinin temelini olusturmaktadir. Bu calismanin amaci, hastalarin hekimleriyle olan iletisiminde guven seviyelerini ve bunu etkileyen unsurlari tespit ederek hasta-hekim iliskisindeki guven unsurunu gelistirmek icin oneriler sunabilmektir. Gerec ve Yontem: Calismaya 305 hasta katilmistir. Hastalarin demografik ve sosyo-ekonomik ozelliklerini, hekimlerine guven ve dermatoloji bolumune olan memnuniyet duzeyleri ile hasta-hekim iliskisi hakkindaki goruslerini degerlendirebilmek icin bir anket formu hazirlanmistir. Anket verilerinin analizinde istatistik paket programlarindan SPSS 15.0 (Statistical Package of Social Science) kullanilmistir. Bulgular: Calismamiza katilan hastalarin hekimlerine guven seviyesi (5 uzerinden) ortalama 3,72 [+ ou -] 0,54 olarak bulunmustur. Bu da hastalarin hekimlerine orta derecenin uzerinde guven duydugunu gostermektedir. Hasta-hekim iliskisinde guven duzeyi ile hastanin yas, cinsiyet ve gelir gibi sosyo-demografik ozellikleri arasinda istatistiksel olarak anlamli bir iliski bulunmamaktadir. Hastalarin memnuniyeti ise yine ortalama 4,17 [+ ou -] 0,65 olarak bulunmustur. Guven ile memnuniyet arasinda pozitif yonde ve guclu bir iliski vardir. Anketin acik uclu sorularindan elde edilen verilere gore hastalarin hekimlerini secerken daha cok hekimin bilgisine, guler yuzlu olusuna dikkat ettikleri tespit edilmistir. Hasta-hekim iliskisinde en onemli unsurun guven oldugu belirtilmistir. Hastalarin; bilgili, sempatik ve durust hekimlere daha cok guvendikleri bunun yaninda guvensizlik yaratan hekim davranislari olarak ilgisizlik, saygisizlik ve hastaya yeteri kadar bilgi verilmemesi tespit edilmistir. Sonuc: Literaturde bu konu oldukca cok arastirilmasina ragmen bizim calismamiz ulkemizde tespit edebildigimiz kadariyla dermatoloji alaninda yapilan ilk guven olcme calismasidir. Bircok kronik hastaliga sahip olan dermatolojide hastalarin tedaviye uyumlarini ve ayni hekim ya da merkeze devamlarini saglamak guven temini ile olabilmektedir. Bu nedenle hasta-hekim iliskisinde guven unsuru gozardi edilmemeli ve guvensizlik yaratacak tutum ve davranislar icerisinde bulunulmamalidir. (Turkderm 2009; 43: 89-94) Anahtar Kelimeler: Dermatoloji, guven, hasta-hekim iliskisi